Thread starter
#1

Hi,

In Reference to

I have the following Practice Questions Hull 5.23:-

1) It states that

3) The third I have is in Part b of this question. It says if

If t=1, shouldn't then h= e^(R-Rf)*(T-

In Reference to

**FIN_PRODS_HULL_CH5_Determination_Of_Forward_and_Futures_Prices_Practice_Question_5.23**:-I have the following Practice Questions Hull 5.23:-

1) It states that

**Ft = St * e ^ (R- Rf ) (T-t)**

Isn't Ft =Isn't Ft =

**S0 * e ^ (R- Rf ) (T-t) ......?**

If we were to expressFt in terms of St, then, Ft= St *If we were to expressFt in terms of St, then, Ft= St *

**e ^ (R-k) *T**

2) If the Hedge Ratio is h, how is the Pricing with hedging h( F0- Ft) + St ...?

2) If the Hedge Ratio is h, how is the Pricing with hedging h( F0- Ft) + St ...?

3) The third I have is in Part b of this question. It says if

**t= 1**day, then h= e^(R-Rf) ***(T-t)**and so h reduces to h= e^(R-Rf) ***T**

If t=1, shouldn't then h= e^(R-Rf)*(T-

**1**) or h= e^(R-Rf)* (**1**) if this is interpreted as (T-t) = 1 ..?

## Stay connected